Ocular Manifestations of Diabetes: A Cross-Sectional Study: Doi: 10.36351/pjo.v39i2.1570 - Moughees Ahmad; Zeeshan Hameed; Irfan Qayyum Malik; Ali Hassan Iqbal; Tanveer Ahmed Choudhary (Pakistan Journal of Ophthalmology, 2023)
Purpose: To describe the ocular manifestations of diabetes mellitus in patients of a tertiary care hospital of Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Ophthalmology Department, DHQ Teaching Hospital, Gujranwala from 1st October, 2022 to 31st December 2022 (3 months). Methods: After taking informed consent and approval from ethical review committee, a self-designed questionnaire was used to collect data which included biodata, type, duration and control of diabetes, associated comorbidities and treatment. Visual acuity and intraocular pressure was measured. Anterior segment examination was performed on slit-lamp bio microscope and posterior segment examination was done with the help of Volk 90D lens after pupillary dilatation with Tropicamide 1% eye drops. All findings were saved on excel spreadsheets and analyzed through Statistical Package for Social Sciences (SPSS) version 25. Results: Out of total 500 patients, 208 (41.6%) were male and 292 (58.4%) were female. Ages ranged from 35 to 77 years with mean age of 55.7 years. Type II diabetes was present in 467 (93.4%) patients and only 147 (29.4%) patients had good glycemic control. Most common anterior segment finding was cataract in 321 (64.2%) patients followed by dry eye and posterior blepharitis in 300 (60.0%), delayed pupillary response in 103 (20.6%) patients. In posterior segment, most common finding was Non-proliferative Diabetic Retinopathy (NPDR) in 90 (18%) patients. Conclusion: Cataract and non-proliferative diabetic retinopathy are the commonest manifestations of diabetes.